Web News 2013 - Språkbanken Text (University of Gothenburg, 2024)
News from Swedish newspapers' websites

Nyheter från svenska dagstidningars webbplatser
Webbnyheter 2013
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik